2002
DOI: 10.1161/hy0202.103441
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen and Its Cleaved Derivatives Inhibit Angiogenesis

Abstract: Abstract-The members of the serine protease inhibitor (serpin) family, which share a common tertiary structure and a role as serin protease inhibitors, are involved in a variety of newly discovered functions. For example, antithrombin III exerts a strong antiangiogenic activity. Angiotensinogen, the renin substrate, has a folded structure and is a member of the noninhibitory serpin subfamily. Two other noninhibitory serpins, maspin and pigment epithelium-derived factor, have antiangiogenic properties. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 31 publications
2
84
0
Order By: Relevance
“…HUVEC tubule formation and migration assay was performed as previously described [52]. Briefly, 200 µl Matrigel (BD Biosciences, Bedford, MA, USA) was pipetted into each well of a 24-well plate and polymerized for 30 min at 37 °C.…”
Section: Huvec Tubule Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…HUVEC tubule formation and migration assay was performed as previously described [52]. Briefly, 200 µl Matrigel (BD Biosciences, Bedford, MA, USA) was pipetted into each well of a 24-well plate and polymerized for 30 min at 37 °C.…”
Section: Huvec Tubule Formation Assaymentioning
confidence: 99%
“…CAM assay was performed with of fertilized chicken eggs (day 6) using a method previously described [52]. A 1-cm diameter window was opened on the egg shell (Yueqin Breeding Co. Ltd, Guangdong, China).…”
Section: Cam Assaymentioning
confidence: 99%
“…AGT and des(AngI)AGT have the ability to inhibit proliferation in well-established models of angiogenesis, including cultured endothelial cells by reducing their capacity to migrate and form capillary-like structures in an artificial matrix. 18 They also reduced neovascularisation in a chicken egg model of angiogenesis, using a recombinant adenovirus carrying the human angiotensinogen gene under the control of the cytomegalovirus promoter (AdAGT). In vitro studies showed that AdAGT selectively inhibited endothelial cell proliferation.…”
Section: Inducing Angiogenesismentioning
confidence: 99%
“…Compared with mammalian models, there is no influence of factors coming from the mother. A possible therapeutic intervention may thus be through administration of antioxidant molecules or regulatory peptides (10).…”
Section: Diabetes Vol 53 March 2004mentioning
confidence: 99%